Personalizing evaluation : a humanist approach to valuing - Kushner, Saville (Emerald Publishing Limited, 2025)
Personalizing Evaluation: A Humanist Approach to Valuing, 3rd Edition proposes an inversion of Program and Person. Rather than portray a Program as a context to understand the person, we portray the individual's life and work as a context for understanding the significance of a Program. Personalizing Evaluation shows, with numerous examples from live data, how this is achieved. This approach to "methodological individualism" also leads to a Humanist approach to evaluation following core Humanist principles of the right to self-determination, democratizing judgment, providing a basis for the justification of authority, and locating the autonomous individual within the moral embrace of the collective. Personalizing Evaluation, therefore, deals extensively with evaluation ethics and issues with validity. As is explored in a dedicated chapter, narrative emerged alongside European Humanism as the methodology of choice, and this underpins the case study approach of the book.
Includes index.
Keywords: Individuality -- Research.; Sociology -- Methodology.; Education -- Organizations & Institutions.; Philosophy and theory of education.; Educational administration and organization.; elektronické knihy; electronic books